Review: John Dugard, Confronting Apartheid. A Personal History of South Africa, Namibia and Palestine, Auckland Park, Jacana, 2018 (Journal of Namibian Studies : History Politics Culture, 2018)
Review: John Dugard, Confronting Apartheid. A Personal History of South Africa, Namibia and Palestine, Auckland Park, Jacana, 2018